Studying reactivity ratios and physical properties of n-vinyl pyrrolidone-N,N’-dimethylacrylamide copolymer - Tan, Phan Minh; Khoi, Nguyen Van; Thang, Tran Vu; manh, Nguyen Van; Phuong, Hoang Thi (Vietnam Journal of Chemistry, 2016)
The copolymers of N-vinyl pyrrolidone (VP) and N,N’-dimethyl acryamide (DMAm) were prepared by free radical polymerization in a ethanol solution, using ammonium persulfate (APS)/ascorbic acid (As) as an initiator. The monomer reactivity ratios were calculated by Kelen-Tudos method using elemental analysis data. The characteristics of the copolymer were studied by IR spectroscopy and DSC, TGA methods. The reactivity ratios obtained rVP = 0.195 and rDMAm = 2.62 showed that content of DMAm was higher than VP in the copolymer. In addition, the results showed that the glass transition temperature of copolymer Tg = 98 oC. Keywords. Copolymer N-vinyl pyrrolidone-co-N,N’-dimethylacryamide, N-vinyl pyrrolidone, N,N’-dimethylacryamide, acryamide derivatives, copolymerization.